Kepastian Hukum dan Perlindungan Investor dalam Investasi Digital Melalui Aplikasi Trading Saham Online di Indonesia - Roberto Sahat Martua Siagian; Zulfikri Pohan; Sayuti Munte (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid development of digital technology has significantly transformed investment activities in Indonesia’s capital market, particularly through the use of online stock trading applications. These applications provide convenience, efficiency, and broader access for the public to participate in digital investment activities. However, along with the increasing number of users, various legal issues have emerged, including data security, investor protection, transaction transparency, and the potential for unlawful activities within digital trading platforms. This study aims to analyze the legal certainty of digital investment through online stock trading applications in Indonesia and to examine the role of regulations in protecting investors within the digital capital market system. The research employs a normative juridical method using a statutory and conceptual approach by analyzing laws, regulations, legal literature, and related legal principles. The findings indicate that Indonesia has established several regulations governing digital investment activities through the capital market framework under the supervision of the Financial Services Authority and the Indonesia Stock Exchange. Nevertheless, challenges remain regarding legal protection, regulatory adaptation to technological advancements, and public legal awareness in digital investment practices. Therefore, stronger legal enforcement, adaptive regulations, and increased investor education are necessary to ensure legal certainty and create a secure digital investment environment in Indonesia.